Real-Time Eye-to-Eye Contact Is Associated With Cross-Brain Neural Coupling in Angular Gyrus - Noah, J. Adam; Zhang, Xian; Dravida, Swethasri; Ono, Yumie; Naples, Adam; McPartland, James C.; Hirsch, Joy (Frontiers in Human Neuroscience, 2020)
Direct eye contact between two individuals is a salient social behavior known to initiate and promote interpersonal interaction. However, the neural processes that underlie these live interactive behaviors and eye-to-eye contact are not well understood. The Dynamic Neural Coupling Hypothesis presents a general theoretical framework proposing that shared interactive behaviors are represented by cross-brain signal coherence. Using functional near-infrared spectroscopy adapted for hyperscanning, we tested this hypothesis specifically for neural mechanisms associated with eye-to-eye gaze between human participants compared to similar direct eye-gaze at a dynamic video of a face, and predicted that the coherence of neural signals between the two participants during reciprocal eye-to-eye contact would be greater than coherence observed during direct eye-gaze at a dynamic video for those signals originating in social and face processing systems. Consistent with this prediction cross-brain coherence was increased for signals within the angular gyrus during eye-to-eye contact relative to direct eye-gaze at a dynamic face video (p < 0.01). Further, activity in the right temporal-parietal junction was increased in the real eye-to-eye condition (p<0.05, FDR corrected). Together, these findings advance a functional and mechanistic understanding of the angular gyrus and cross-brain neural coupling associated with real-time eye-to-eye contact.